Synthesis and physico-chemical study of multifunctional cardo epoxy resin and its jute fiber reinforced silica filled and unfilled composites - Patel PJignesh; Adroja P Pooja; Aparsania PH (Journal of Polymer Materials, 2013)
Multifunctional epoxy resin (EBCF) was synthesized by in situ alkali catalyzed condensation of bisphenol-C, formaldehyde and epichlorohydrin and cured using 20;tetrahydrophthalic anhydrid at 100dC. Cured and uncured resins were characterized by FTIR and HNMR spectroscopic techniques, DSC and TGA at 10dCmin-1 heating rate in nitrogen atmosphere. Both EBCF and EBCF- THPA followed multistep and two step functional order decomposition kinetics, respectively. Jute-EBCF and silica filled composites have been fabricated by hand layup technique under 27.58 MPa pressure at 135dC for 4h. tensile and flexural properties are discussed in light of filler content. Chemical resistance of Jute-EBCF composite in water, acid and saline environments were studied at 35dC and it is observed that it possesses excellent chemical resistance even in harsh acid and saline environments.
Keywords: Composites; Curing; Kinetic parameters; Multifunctional epoxy resin; water absorption